Youth labor in transition inequalities, mobility, and policies in Europe - O'Reilly, Jacqueline 1964-; Leschke, Janine 1976-; Ortlieb, Renate; Seeleib-Kaiser, Martin 1964-; Villa, Paola 1949- (Oxford University Press, 2019)
"Youth transitions to employment in Europe are increasingly protracted, precarious and differentiated by gender, ethnicity, and socioeconomic status. Examining employment transitions affected by the family and migration the authors argue for an integrated analysis of the sphere of economic production and social reproduction if policy intervention is to be effective"...
Keywords: Youth -- Employment -- Europe; Young adults -- Employment -- Europe; Labor policy -- Europe; School-to-work transition -- Europe; Jugendlicher Arbeitnehmer; Europa; Aufsatzsammlung